If you expand the desired form, you get
[tex]a\sin(bx+c)=a(\sin bx\cos c+\cos bx\sin c)[/tex]
and if we match this up with the given form, we can see that [tex]b=4[/tex], and we have to find [tex]a[/tex] and [tex]c[/tex] such that
[tex]\begin{cases}a\cos c=-6\\a\sin c=-2\end{cases}[/tex]
If we divide the second equation by the first, we have
[tex]\dfrac{a\sin c}{a\cos c}=\dfrac{-2}{-6}\iff\tan c=\dfrac13[/tex]
If we assume [tex]-\dfrac\pi2<c<\dfrac\pi2[/tex], then we can take the inverse tangent of both sides to get [tex]c=\tan^{-1}\left(\dfrac13\right)[/tex]. If we do this, then we find
[tex]a\sin\left(\tan^{-1}\left(\dfrac13\right)\right)=\dfrac a{\sqrt{10}}=-2\implies a=-2\sqrt{10}[/tex]
So we can rewrite
[tex]y=-6\sin4x-2\cos4x[/tex]
as
[tex]y=-2\sqrt{10}\sin\left(4x+\tan^{-1}\left(\dfrac13\right)\right)[/tex]